2020
DOI: 10.1016/j.cub.2019.11.071
|View full text |Cite
|
Sign up to set email alerts
|

Changing Climate Drives Divergent and Nonlinear Shifts in Flowering Phenology across Elevations

Abstract: Highlights d Flowering time is diverging among communities across an elevational gradient d Divergence reflects nonlinear shifts in flowering phenology over three decades d Climatic variables have also changed differently across space and over time d Changing climate is driving phenological reshuffling across local spatial gradients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
61
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 66 publications
7
61
1
Order By: Relevance
“…Menzel et al (2006) and Wang et al (2015) observed greater sensitivity to climate warming in populations from warmer environments, which should reduce synchrony among populations, and therefore potential gene flow, with warming. In contrast, Rafferty et al (2020) observed species‐specific decreases or increases in synchrony of flowering between populations at different elevations. However, these long‐term studies did not allow direct estimation of overlap in flowering time distributions, but rather relied on first or mean flowering dates to describe population flowering phenology, despite weak correlations of these parameters with other attributes of flowering phenology (CaraDonna et al, 2014).…”
mentioning
confidence: 90%
“…Menzel et al (2006) and Wang et al (2015) observed greater sensitivity to climate warming in populations from warmer environments, which should reduce synchrony among populations, and therefore potential gene flow, with warming. In contrast, Rafferty et al (2020) observed species‐specific decreases or increases in synchrony of flowering between populations at different elevations. However, these long‐term studies did not allow direct estimation of overlap in flowering time distributions, but rather relied on first or mean flowering dates to describe population flowering phenology, despite weak correlations of these parameters with other attributes of flowering phenology (CaraDonna et al, 2014).…”
mentioning
confidence: 90%
“…During the last decade, elevational gradients have been increasingly used as a framework for studying environmental impacts on plant and pollinator communities (e.g., Adedoja, Kehinde, & Samways, 2018; Lara‐Romero, Seguí, Pérez‐Delgado, Nogales, & Traveset, 2019; Rafferty et al., 2020). Oftentimes changes in plant–pollinator interactions observed along elevational gradients appear to arise through changes in the respective species pools (Adedoja et al, 2018; Brittain, Kremen, & Klein, 2013; Lara‐Romero et al, 2019; Maglianesi, Blüthgen, Böhning‐Gaese, & Schleuning, 2015; Partida‐Lara et al, 2018; Simanonok & Burkle, 2014), with communities at higher elevations being characterized by less species and more generalized interactions (e.g., Hoiss et al., 2015; Ramos‐Jiliberto et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, neutral and facilitative effects have also been observed (Gilpin, Denham, & Ayre, 2019;Holzschuh, Dormann, Tscharntke, & Steffan-Dewenter, 2011;Lázaro, Lundgren, & Totland, 2009). At present, climate change is shifting not only the phenology of individual species, but also the relative phenology of interacting species (CaraDonna, Iler, & Inouye, 2014;Høye, Post, Schmidt, Trøjelsgaard, & Forchhammer, 2013;Kudo & Cooper, 2019;Rafferty, Diez, & Bertelsen, 2020). Thus, individual species have to simultaneously adjust both to new abiotic conditions and to changes in the species with which they interact (Burkle & Alarcón, 2011;Kaiser-Bunbury, Muff, Memmott, Müller, & Caflisch, 2010;Saavedra, Rohr, Olesen, & Bascompte, 2016).…”
mentioning
confidence: 99%
“…Climate change has induced earlier reproduction among spring-flowering angiosperms [64,66,80,97]. Climate-change mediated selection generally favors earlier flowering, but at differing rates among populations across elevational gradients [69,70] and geographic regions [98]. Several key questions remain unresolved:…”
Section: Reproductive Phenologymentioning
confidence: 99%